An action research intervention in an internal medicine service - Costa, P.; Passos, A. M.; Silva, S.A.; Ramos, S.; Leite, E.S. (1st International Meeting on Wellbeing and Performance in Clinical Practice, 2014)
Background: In this presentation we will describe a specific case of an action research conducted in an Internal Medicine service at a large teaching Hospital and discuss its practical implications. Methods: The service involved in the action research has 59 doctors, 66 nurses, and 42 auxiliary professionals, divided by four sectors. The present intervention focused on one of those sectors. Findings: On a first phase, the problem was identified and defined. In order to do so, researchers conducted interviews with key persons (chief nurse, chief of sector) and with diverse professionals. There were also moments of observations, where researchers were collecting data in loco by observing the daily routine of the service. Finally, quantitative data was gathered using a short questionnaire encompassing key dimensions (e.g. conflict, teamwork). This particular sector reports a high level of conflict within and between different professional groups, particularly between nurses and doctors, as well as a lack of communication and cooperation between them. Discussion: The action was planned together with the professionals, who were also responsible for its implementation. The evaluation of the action research will be presented, as well as a reflection of what worked and what did not work.